Inferno in Chechnya: the Russian-Chechen wars, the Al Qaeda myth, and the Boston Marathon bombings - Williams, Brian Glyn (ForeEdge, 2015)
"Details the history behind the Russian treatment of Chechens, the series of wars, the actual role of Arab fighters, and the Boston Marathon bombers, who are profiled in the final chapter"--Provided by publisher